Gender-based comparison of nutritional status in tribal and non-tribal populations: a study in the Udaipur region - Tripathi, Nisha; Satyanarayana , P. (International Journal of Research in Medical Sciences, 2024)
Background: It is imperative to examine the nutritional quality of adult populations, both tribal and non-tribal, in the Udaipur region of Rajasthan in order to comprehend the health dynamics of these societies. Tribal communities frequently encounter particular difficulties with regard to healthcare access, socioeconomic standing, and cultural customs that may have an impact on their nutritional well-being that is distinct from that of non-tribal communities. Methods: Our study group consisted of 300 tribals and 300 non tribals. The blood was tested to determine various nutritional parameters like minerals iron, calcium, phosphorus, magnesium, and vitamins like vitamin, vitamin A, vitamin D, and vitamin B12. Results: Comparable levels of parameters like calcium, magnesium, phosphorus, vitamin A, and vitamin D3 were found in both non-tribal and tribal people, suggesting that both groups’ nutritional statuses were generally similar. Non-tribal males and females exhibited significantly higher iron levels compared to their tribal counterparts. Both non-tribal males and females had considerably higher levels of vitamin C and B12 compared to tribal peers. Conclusions: The study highlights the differences in iron, vitamin C, and vitamin B12 levels that occur in the Udaipur region between non-tribal and tribal individuals.